Hubungan Kelentukan Pergelangan Tangan Dengan Kemampuan Shooting Permainan Bolabasket Pada Mahasiswa Program Studi Pendidikan Olahraga ISDIK Kie Raha Maluku Utara - Akhmady, Alief Lam (Peneliti.net, 2024)
This study aims to determine the relationship with the formation of the wrist with the ability to shoot in the bolabasket game in students of the ISDIK Kie Raha Maluku Utara Sports Education Study Program in Ternate City. This research is a correlational research. The subjects in this study were students of the 2023 Sports Education Study Program ISDIK Kie Raha Maluku Utara, totaling 20 students. The hypothesis test consists of a product moment correlation from Pearson at a significance level α = 0.05 and multiple correlation tests or multiple regression using the SPSS 16.0 computer program. The results of this study concluded that in the 2023 Sports Education Study Program ISDIK Kie Raha Maluku Utara: (1) There is a significant relationship with the formation of the wrist with shooting capabilities as evidenced by the value of R Product Moment (0.869)> R Table (0.456).